Reproducibility of tactile assessments for children with unilateral cerebral palsy - Auld, M.; Ware, R.; Boyd, Roslyn; Moseley, G.; Johnston, L. (2012)
A systematic review identified tactile assessments used in children with cerebral palsy (CP), but their reproducibility is unknown. Sixteen children with unilateral CP and 31 typically developing children (TDC) were assessed 24 weeks apart. Testretest percent agreements within one point for children with unilateral CP (and TDC) were Semmes-Weinstein monofilaments: 75% (90%); single-point localization: 69% (97%); static two-point discrimination: 93% (97%); and moving two-point discrimination: 87% (97%). Testretest reliability for registration and unilateral spatial tactile perception tests was high in children with CP (intraclass correlation coefficient [ICC] = 0.790.96). Two tests demonstrated a learning effect for children with CP, double simultaneous and tactile texture perception. Stereognosis had a ceiling effect for TDC (ICC = 0) and variability for children with CP (% exact agreement = 47%50%). The Semmes-Weinstein monofilaments, single-point localization, and both static and moving two-point discrimination are recommended for use in practice and research. Although recommended to provide a comprehensive assessment, the measures of double simultaneous, stereognosis, and tactile texture perception may not be responsive to change over time in children with unilateral CP. © 2012 Informa Healthcare USA, Inc.